TRANSCRIPTOMIC ANALYSIS OF BLACK SOYBEANS (GLYCINE MAX (L.) MERR.) LOCAL VARIETIES AND THE F4 RECIPROCAL CROSSING PROGENIES - Iftikhor Amany, Royyan
Black soybean (Glycine max (L.) Merr.) is a highly-valued commodity due to its flexibility that can be used to fulfill multiple aspects of human needs, such as being a primary source of food, supplementary medicine ingredients, and as a source of alternative energy. Further development of this plant through plant breeding could benefits humanity in a widespread manner. In this study, research was conducted to analyze the gene expression profile of two black soybeans (Glycine max (L.) Merr.) local varieties and its F4 progeny through transciptomic analysis, to supplement the ever-expanding study of black soybeans plant breeding. Four sample groups, each complemented by three biological replicates, was used in this study. RNA-seq sequence data of the twelves samples used were acquired from previous experiment (Sumardi et al., 2019). The research methods used includes, data quality check, pre-processing, read mapping/alignment, read quantification, DEG (differentially expressed genes) analysis, and data visualisation. Quality check of all the samples sequences post pre-processing shows varying read counts, ranging from 23.7-34.7 (million) reads, and a phred score between 34-36, indicating a good quality sequences. Read mapping/alignment statistics shows a high mapping proportion, between 97.7-98.7% mapped. Among all the mapped fragments, 91.9 – 94% were found to be a uniquely-mapped fragments. Principal component analysis (PCA) results shows two genes with the most significant impact from each of the two principal component, LOC100775188 & LOC100798239. Both were found to have roles in plants response towards biotic/abiotic stress. Similar functions were shown by the highest read counts among the uniquely expressed genes from each sample group, based on venn diagram visualisation. Differential analysis (q-value ? 0,05 & Log2FC ? |2|) of six comparison scenario between two sample groups shows eleven counts of differentially expressed genes, contributed by four different genes, that is LOC102670366, LOC102664051, LOC100816226, and LOC121172865, found only on Parental1 and Filial4-1 groups. In conclusion, data read count visualisation and differential analysis shows differentiation between parental and filial sample groups based on their gene profile expression, with some genes, especially ones that played role in plant growth and development, and plants response to biotic/abiotic stress, showing clearer distinction between those two sample groups. The relative upregulation of genes LOC102670366, LOC102664051, LOC100816226, and LOC121172865 expression found only on Parental1 and Filial4-1 groups indicates a character inheritance pattern influenced by female parental in the crossing design.